O esgotamento das imagens: em A última palavra é a penúltima 2.0, do Teatro da Vertigem, Mal visto mal dito e Pra frente o pior, de Samuel Beckett - Silva, Eduardo Reis (2019)
The present master's research proposes a comparison between the visualscenic intervention The last word is the penultimate 2.0 (2014), of the Brazilian group Teatro da Vertigem, and the prose work Ill seen ill said (1981), and Worstward Ho (1983), by the Irish playwright and writer Samuel Beckett. The aim here is to analyze how the scenic intervention manages to update the Beckettian universe through the exhaustion of the images. We can verify that the Beckettian narrative in Ill seen ill said and Worstward Ho, tries all the time to mark an exhaustion of language by establishing repetitions of phrases, themes and ideas - as if this uninterrupted repetition would propose an oscillation between fatigue and exhaustion of words / images. However, in the scenic intervention, the Teatro da Vertigem also seems to propose that same oscillation; however, it is verified here an exhaustion of the image, caused by the excess of scenes, resulting in the nullification of the total reception of the spectator, thus creating a kind of multidimensional visibility, with layers and layers of scenes that overlap each other. To deepen these questions, some concepts of the French philosopher, Gilles Deleuze, will be used; on the Beckettian universe, the reflections of Fábio de Souza Andrade, Peter Pál Perlbart, Ana Helena Souza and Lívia Bueloni Gonçalves will be of great value and, on the performativity studies, we have the support of the ideas of Josette Féral, Erika Fischer-Lichte and Eleonora Fabião